ANALISIS HARGA POKOK PRODUKSI ABON IKAN BANDENG PADA IKM D'PORE MEME KABUPATEN SITUBONDO - Sari, Lita Permata; Ediyanto, Ediyanto; Ardiansyah, Johan Putra Pradana (Growth, 2024)
Calculation of the cost of production is an important part of Small and Medium Industries because it really helps the industry explain how to determine the selling price of products. The product of this research is shredded milkfish from IKM D'Pore Meme. This research uses a qualitative approach. The data used is primary data. Based on the research results, it shows that there is a difference in the calculation of the cost of production at IKM D'Pore Meme and the calculation of the cost of production using the Full Costing method.